Žalgiris: neatsakyti klausimai - Bumblauskas, Alfredas (Lietuvos istorijos studijos, 2010)
The aim of the article is, on the basis of the hints found in the sources and Sven Ekdahl’s hypothesis, to look at the battle of Žalgiris (Grunwald) as a typical fight of medieval knights, the conceptions of the nature of which in historiography, ignoring the issues of tactics, are obviously outdated. And this, in its turn, leads to strongly emphasizing the necessity for more thorough investigations into tactics. Today it is recognized that critical studies of the battle of Grunwald started in the seventh decade of the 20th century only, because until that time images coming from national mythologies prevailed in the studies of the battle of Grunwald, which dictated conditions to the historians of the "scissors and glue" method who cut patterns from the Chronicle of Jan Długosz. The author of the critical turning point, Sven Ekdahl, made the following maxim: to get rid of the Chronicle of Jan Długosz, to carry out a systematic analysis of the sources, and to create a critical reconstruction of the battle of Grunwald that is independent of most various ideologems. Nevertheless, Sven Ekdahl’s hypotheses have not acquired a systematic form, which could create the new narrative of the battle of Grunwald. This, as well as gaps in critical science of history on the whole, determine the fact that images of the collective memory, which were much stronger influenced by and still are under the influence of works of art of the undisciplined imagination, have not been significantly affected. Sven Ekdahl has drawn the following most general conclusion: the role of the army of the Grand Duchy of Lithuania in the battle was not inferior in anything to the Polish army, and in some aspects it even surpassed the latter. Sven Ekdahl based this statement on the new sources, on the letter of 1413, in particular, which spoke directly about the maneuver of the army of the Grand Duchy of Lithuania and participation of the Lithuanian party in trophy sharing. The latter subject is also supplemented with other aspects, especially with administration of the occupied castles of the Order and the eventual partition of the Order’s territory. Sven Ekdahl’s statements are "amortized" in Polish historiography from various aspects, and they are excessively glorified by the Lithuanians. Criticism is lacking in both cases because Ekdahl’s hints about the medieval tactics in the battle of Grunwald are disregarded. This means that the themes of the tactics of three corps ("drei Treffen"), the gonfanons, and wedge formations, which enable us to look anew both at the level, composition, formation of the army of the Grand Duchy of Lithuania and its action in the battlefield. The sources unambiguously speak about three corps of the army of the Grand Duchy of Lithuania whose gonfanons could contain two major heraldic signs - Vytis (the State emblem of Lithuania - the White Knight astride a leaping stallion) and the Pillars of Gediminaičiai (one of the major symbols of statehood), as well as forming of corps in wedges. The quantity of the heavy mounted soldiers in the tactics of wedge is not decisive - to form spearheads of three corps or wedges the heavy mounted soldiers from the Duke’s elite could have sufficed Lithuania, especially having in mind Vytautas’ attempts to modernize the army of the Grand Duchy of Lithuania before the battle. Formation in three wedges allows us to imagine the "Lithuanian" phase of the battle in a different way, to interpret the riddle of the flags of Smolensk in a different way. They are thought to be flags of the third reserve wedge that remained in the battlefield. The mercenaries from the advanced post castles of the Grand Duchy of Lithuania who were armed best could have been in that wedge. Since Poles could have dominated among the mercenaries - at least the composition of the very garrison of Smolensk shows this and Długosz also knew about it - this brings sufficiently new aspects of interpretation into the motives of this chronicler of the glorification of the flags of Smolensk in the battlefield of Grunwald.